Cephalometric Norms of Bangladeshi Young Children Based on McNamara’s Analysis (Update Dental College Journal, 2022)
Objective: To evaluate the cephalometric norms of Bangladeshi young children using McNamara’s analysis.Methods: It was a descriptive cross-sectional study carried out in the Department of Orthodontics, BSMMU among the dental patients visiting Dental OPD of BSMMU. The test sample was 40 Cephalometric radiographs of patients of which 20 were boys (group I) and 20 were girls (group II). The study respondents were of Bangladeshi origin, aged between 11 and 18 years at the time of cephalometric radiograph taken. A randomized sampling technique was followed to collect samples.Results: The mean cephalometric values of McNamara variables were measured and compared with the Caucasian children and Bangladeshi adults. The p values of all variables for Group I (boys) and Group II (girls) were more than 0.05 which was not significant. So it was interpreted that there was no significant difference in the values of McNamara variables between Bangladeshi boys and girls. But in comparison to Caucasian children the p-value of all the variables was significant (